Community Partnership Empowerment: Optimizing the Teaching Profession Through Omohage Application Based e-Modules Preparation Training - Indah Setyo Wardhani; Ika Dian Rahmawati; Bian Dwi Pamungkas (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This service activity was carried out against the background of the facts: (1) the gap in the quality of education in rural and urban areas; (2) the need for Information and Communication Technology (ICT)-based learning to face the demands of the 21st century, the industrial revolution 4.0, and the digital era; and (3) teachers have difficulty in preparing IT-based learning tools. The Community Partnership Programme team from DRTPM offers a solution by implementing training activities for preparing e-modules to implement spatial imaginative learning models through the omohage (Online Handbook Web-based) application. The participants were all teachers of SDIT AL Kautsar and PAUD AL Kautsar, Kebonduren village, Ponggok sub-district, Blitar district, East Java. Training activities were carried out using the method of discussion, lecture, and practice of handbook preparation by participants. The stages of the activity were: (1) preparation stage, (2) implementation stage, and (3) evaluation stage. The results of the activities are: (1) teachers' understanding of the use of the omohage application; (2) increased teacher skills in preparing learning tools assisted by the omohage application; and (3) published teacher handbook products online.